2010
DOI: 10.1093/schbul/sbq118
|View full text |Cite
|
Sign up to set email alerts
|

Resequencing and Association Analysis of the KALRN and EPHB1 Genes And Their Contribution to Schizophrenia Susceptibility

Abstract: Background: Our genome-wide association study of schizophrenia found association signals at the Kalirin gene (KALRN) and EPH receptor B1 gene (EPHB1) in a Japanese population. The importance of these synaptogenic pathway genes in schizophrenia is gaining independent supports. Although there has been growing interest in rare (<1%) missense mutations as potential contributors to the unexplained heritability of schizophrenia, there are no population-based studies targeting rare (<1%) coding mutations with a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 37 publications
(41 reference statements)
2
75
1
Order By: Relevance
“…In contrast, total levels of kalrin-5, kalirin-12, and PAK1 were not affected [78;79]. Finding altered kalirin-9 in schizophrenia is supported by prior reports that rare missense mutations located within the region of the KALRN gene shared only by kalirin-9 and -12 have been associated with risk for schizophrenia [80]. Deo et al further evaluated the effects of sustained (2 week) over-expression of kalirin-9 in mature primary neuronal cultures.…”
Section: Possible Causes Of Dendritic Spine Loss In Schizophreniamentioning
confidence: 64%
See 1 more Smart Citation
“…In contrast, total levels of kalrin-5, kalirin-12, and PAK1 were not affected [78;79]. Finding altered kalirin-9 in schizophrenia is supported by prior reports that rare missense mutations located within the region of the KALRN gene shared only by kalirin-9 and -12 have been associated with risk for schizophrenia [80]. Deo et al further evaluated the effects of sustained (2 week) over-expression of kalirin-9 in mature primary neuronal cultures.…”
Section: Possible Causes Of Dendritic Spine Loss In Schizophreniamentioning
confidence: 64%
“…Rare mutations in in the kalirin-9 sequence have been associated with risk for schizophrenia, possibly by altering activity of kalirin’s RhoA GDP/GTP exchange factor function. [80] Using this approach, it would be possible to model both common disease related increases in kalirin-9 levels and rare disease-associated kalirin mutations, providing the potential to reveal both proximate and early causal steps in pathogenesis. Because most evidence suggests that cortical gray matter volume reductions within individuals with schizophrenia emerge as an acceleration of the normal developmental trajectory during adolescence and early adulthood, the assessment of such models should evaluate this developmental phase closely.…”
Section: Discussionmentioning
confidence: 99%
“…191 The KALRN locus is associated with risk for schizophrenia 192 and missense mutations have also been reported in a small cohort. 193 Various actin cytoskeleton signaling pathways pertinent to CDC42 (e.g., CDC42-CDC42EP, CDC42-PAK-LIMK, and CDC42-NWASP-ARP2/3) are perturbed selectively in dlPFC layer III pyramidal cells in schizophrenia. 121,191,194,195 In addition, de novo mutations in schizophrenia are overrepresented among loci encoding cytoskeleton-associated proteins that modulate actin filament dynamics, actin bundle assembly, interconnected with activity-regulated cytoskeleton-associated protein (ARC) and NMDAR signaling and could contribute to the pathogenesis of the illness.…”
Section: Relevance Of Dynamic Network Connectivity To Schizophreniamentioning
confidence: 99%
“…Some copy number variants (CNVs) are clear examples of the existence of rare variants of moderate to high effect (Rees et al, 2014). Nevertheless, in general, attempts to identify rare single nucleotide variants (SNVs) associated to schizophrenia did not success (Crowley et al, 2013;Hu et al, 2014;Kenny et al, 2014;Need et al, 2012;Purcell et al, 2014), although some promising results has been found (Kimura et al, 2015;Kushima et al, 2012).…”
Section: Introductionmentioning
confidence: 99%